2006
DOI: 10.1152/ajprenal.00140.2005
|View full text |Cite
|
Sign up to set email alerts
|

A causal role for uric acid in fructose-induced metabolic syndrome

Abstract: The worldwide epidemic of metabolic syndrome correlates with an elevation in serum uric acid as well as a marked increase in total fructose intake (in the form of table sugar and high-fructose corn syrup). Fructose raises uric acid, and the latter inhibits nitric oxide bioavailability. Because insulin requires nitric oxide to stimulate glucose uptake, we hypothesized that fructose-induced hyperuricemia may have a pathogenic role in metabolic syndrome. Four sets of experiments were performed. First, pair-feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
758
5
31

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 955 publications
(860 citation statements)
references
References 41 publications
42
758
5
31
Order By: Relevance
“…Because insulininduced glucose utilization involves not only the stimulation of key metabolic pathways in insulin-sensitive cells but also a NO-dependent increase in muscle blood flow [41], it was proposed that inhibition of the vascular effects of insulin by uric acid was involved in fructose-induced insulin resistance. In support of this hypothesis the development of insulin resistance was prevented by lowering uric acid concentrations with an uricosuric agent in fructose-fed rats [42]. …”
Section: What Are the Mechanisms Responsible For Fructose-induced Metmentioning
confidence: 79%
“…Because insulininduced glucose utilization involves not only the stimulation of key metabolic pathways in insulin-sensitive cells but also a NO-dependent increase in muscle blood flow [41], it was proposed that inhibition of the vascular effects of insulin by uric acid was involved in fructose-induced insulin resistance. In support of this hypothesis the development of insulin resistance was prevented by lowering uric acid concentrations with an uricosuric agent in fructose-fed rats [42]. …”
Section: What Are the Mechanisms Responsible For Fructose-induced Metmentioning
confidence: 79%
“…Masuo et al 4 showed that SUA predicts weight gain in humans and experimental animal studies have shown that allopurinol (a SUA-lowering drug) prevents both fructose-induced hyperuricaemia and weight gain. 23 Based on these results, it is difficult to differentiate whether hyperuricemia directly causes obesity or both hyperuricemia and obesity share a common cause, that is, increased fructose intake. Thus, it could be that obesity is in the causal pathway between SUA and BP and controlling for adiposity would explain the attenuation seen in the effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to raising blood pressure, recent studies support uric acid as having a role in insulin resistance and obesity [ 88,89 ]. Indeed, fructose, which rapidly raises uric acid, induces metabolic syndrome in animals and this can be ameliorated by lowering uric acid [ 88 ].…”
Section: Uric Acid and Blood Pressurementioning
confidence: 99%
“…There are now extensive studies showing that a high uric acid independently predicts the development of hypertension [82][83][84]; likewise, an elevated uric acid is common in early hypertension and was present in almost 90% of hypertensive adolescents in one study [ 85 ]. Furthermore, recent clinical trials have found that lowering uric acid lowers blood pressure in both adolescents and adults with hypertension (and D Feig and R Johnson, unpublished)[ 86,87 ].In addition to raising blood pressure, recent studies support uric acid as having a role in insulin resistance and obesity [ 88,89 ]. Indeed, fructose, which rapidly raises uric acid, induces metabolic syndrome in animals and this can be ameliorated by lowering uric acid [ 88 ].…”
mentioning
confidence: 97%